Hypertension prevalence, awareness, treatment and control in 2019 in the adult population of Mayotte. (23rd February 2022) - Calas, Lucinda; Subiros, Marion; Ruello, Marc; Hassani, Youssouf; Gabet, Amélie; Angue, Marion; Pointeau, Odile; Olié, Valérie; Grave, Clémence
Abstract: Background: Mayotte is a French overseas territory with significant socio-economic and health challenges. This study updates the prevalence of hypertension in Mayotte to estimate the awareness, treatment and control of this disease and identify any associated factors. Methods: Data were taken from the cross-sectional Unono Wa Maore survey conducted in Mayotte in 2019. Analyses were based on the adult population aged 18–69 years who underwent a clinical examination with at least two blood pressure measurements ( n = 2620). Results: In 2019, the prevalence of hypertension was estimated at 38.4% (36.1–40.7%) in the Mayotte population aged 18–69 years. The prevalence was similar in men (38.5%) and women (38.3%; P = 0.95). The prevalence of certain risk factors was high, with 75% of hypertensives being overweight or obese, 13% reporting diabetes and 69% being occupationally inactive. Among the hypertensives, 48% was aware of their diagnosis, with women more likely to be aware than men ( P < 0.0001). Of those who were aware, 45% were treated pharmacologically and 49% reported engaging in physical activity to lower their blood pressure. The control rate was 30.2% among pharmacologically treated hypertensives. Overall, 80% of hypertensive patients had too high blood pressure during the survey's clinical examination. Conclusion: The prevalence of hypertension remains high in Mayotte, where certain risk factors like obesity are particularly common in the population. Awareness, treatment and control remain insufficient. Primary prevention measures, access to a healthy food, and screening and treatment of hypertension should be encouraged by targeting the most affected populations.